Three-dimensional reconstruction and morphometric analysis of mandible of Hamdani sheep: A computed tomography (CT) study - Güzel, Barış Can; Demırcıoglu, Ismaıl; İnce, Nazan Gezer (My University, 2023)
In this study, anatomical, morphometric and volumetric analyses of the mandible of Hamdani sheep were performed using computed tomography (CT) and three-dimensional (3D) software. For this purpose, 16 (eight males, eight females) Hamdani sheep heads were used. Images of these heads were taken on a 64-detector CT device applying 80 kV, 200 MA, 639 mGY, and 0.625 mm section thickness. Scan images of the mandible of each subject were converted into three-dimensional models using 3D software and reconstructed. Surface, volume and linear measurements (24) of the mandible were performed on the models. All the measurements were expressed as mean ± SD. The examinations determined that the mandible's volume and surface area values were more significant in males than females. Mandible length (GOC-ID) was 169.01±0.74 mm, and its height (GOV-CR) was 95.50±0.64 mm in males. In morphometric evaluations, statistically significant differences were observed between males and females in L2 (PC-ID), L6 (GOC-FMN), L14 (MTR-MH), L19(SI), Volume and Surface area measurement parameters (P<0.05). It is thought that the morphometric data obtained will be a reference in pathological conditions, taxonomy studies, and interventional surgical treatment applications to be performed on the site.
Keywords: Computed tomography; Morphometry; Reconstruction; Mandible; Hamdani sheep